Systems analysis of miRNA biomarkers to inform drug safety - Amy L. Schofield; Joseph P. Brown; Jack Brown; Ania Wilczynska; Catherine Bell; Warren E. Glaab; Matthias Hackl; Lawrence Howell; Stephen Lee; James W. Dear; Mika Remes; Paul Reeves; et al. (Archives of Toxicology, 2021)
microRNAs (miRNAs or miRs) are short non-coding RNA molecules which have been shown to be dysregulated and released into the extracellular milieu as a result of many drug and non-drug-induced pathologies in different organ systems. Consequently, circulating miRs have been proposed as useful biomarkers of many disease states, including drug-induced tissue injury. miRs have shown potential to support or even replace the existing traditional biomarkers of drug-induced toxicity in terms of sensitivity and specificity, and there is some evidence for their improved diagnostic and prognostic value. However, several pre-analytical and analytical challenges, mainly associated with assay standardization, require solutions before circulating miRs can be successfully translated into the clinic. This review will consider the value and potential for the use of circulating miRs in drug-safety assessment and describe a systems approach to the analysis of the miRNAome in the discovery setting, as well as highlighting standardization issues that at this stage prevent their clinical use as biomarkers. Highlighting these challenges will hopefully drive future research into finding appropriate solutions, and eventually circulating miRs may be translated to the clinic where their undoubted biomarker potential can be used to benefit patients in rapid, easy to use, point-of-care test systems.

A cost-effective high-throughput microcosm system for studying nitrogen dynamics at the plant-microbe-soil interface - E. Inselsbacher; K. Ripka; S. Klaubauf; D. Fedosoyenko; E. Hackl; M. Gorfer; R. Hood-Novotny; N. Von Wirén; A. Sessitsch; S. Zechmeister-Boltenstern; W. Wanek; J. Strauss (Plant and Soil, 2009)

Distribution and origin of steroid hormones in the yolk of Japanese quail eggs (Coturnix coturnix japonica) - R. Hackl; V. Bromundt; J. Daisley; K. Kotrschal; E. Mstl (Journal of Comparative Physiology B, 2003)

Nitrogen dynamics in different types of pasture in the Austrian Alps - E. Hackl; S. Zechmeister-Boltenstern; E. Kandeler (Biology and Fertility of Soils, 2000)